Cholinergic autoantibodies from primary Sjögren’s syndrome modulate submandibular gland Na+/K+-ATPase activity via prostaglandin E2 and cyclic AMP - Passafaro, Daniela (2010)
We demonstrate that patients with primary Sjögren’s syndrome (pSS) produce functional IgG autoantibodies that interact with the glandular M3 muscarinic acetylcholine receptors (mAChRs). These autoantibodies act as a partial muscarinic agonist, increasing prostaglandin E2 (PGE2) and cyclic AMP production through modifying Na+/K+-ATPase activity, but also interfere with the secretory effect of the parasympathetic neurotransmitter. The IgG from patients with pSS has two effects on the submandibular gland. On the one hand, it may act as an inducer of the proinflammatory molecule (PGE2) that, in turn, inhibits Na+/K+-ATPase activity. On the other hand, it plays a role in the pathogenesis of dry mouth, abolishing the Na+/K+-ATPase inhibition and the net K+ efflux stimulation of the salivary gland in response to the authentic agonist pilocarpine, decreasing salivary fluid production.